2020
DOI: 10.1177/1077801220945035
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Pornography Consumption, Alcohol Use, and Sexual Victimization

Abstract: While research in recent years has investigated the influence of pornography consumption on sexually aggressive behavior, research on the relationship between pornography and experienced victimization is sparse. The current study sought to explore female sexual victimization and its relationship with pornography consumption and alcohol use at two universities ( N = 483). Binary logistic regression analyses indicate that both pornography and alcohol consumption were unique predictors of self-reported victimizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Most of the studies measured all these factors by means of a few items: for example, 1 item (de Heer et al, 2020; Dong et al, 2013; Hagen et al, 2018; Kohut et al, 2020; Malamuth et al, 2012; Spadine et al, 2020; Wright & Tokunaga, 2016), 2 items (Huntington et al, 2021; Leemis et al, 2019; Simons et al, 2012; Stanley et al, 2018), 3 items (Brown & L’Engle, 2009; Huntington et al, 2022), 4 items (Kernsmith & Kernsmith, 2009; Tomaszewska & Krahé, 2018), 5 items (Carr & VanDeusen, 2004), 6 items (Franklin, 2013; Goodson et al, 2020), 7 items (Chang et al, 2016; Mikorski & Szymanski, 2017), or 8 items (D’Abreu & Krahé, 2014; D’Abreu & Krahé, 2016; Lam & Chan, 2007), with one outlier assessing 46 items (Gonsalves et al, 2015). Seven studies used validated instruments to assess the use of pornography or violent pornography (Hald & Malamuth, 2015; Hughes et al, 2020; Huntington et al, 2022; Mikorski & Szymanski, 2017; Palermo et al, 2019; Rostad et al, 2019; Shin & Lee, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the studies measured all these factors by means of a few items: for example, 1 item (de Heer et al, 2020; Dong et al, 2013; Hagen et al, 2018; Kohut et al, 2020; Malamuth et al, 2012; Spadine et al, 2020; Wright & Tokunaga, 2016), 2 items (Huntington et al, 2021; Leemis et al, 2019; Simons et al, 2012; Stanley et al, 2018), 3 items (Brown & L’Engle, 2009; Huntington et al, 2022), 4 items (Kernsmith & Kernsmith, 2009; Tomaszewska & Krahé, 2018), 5 items (Carr & VanDeusen, 2004), 6 items (Franklin, 2013; Goodson et al, 2020), 7 items (Chang et al, 2016; Mikorski & Szymanski, 2017), or 8 items (D’Abreu & Krahé, 2014; D’Abreu & Krahé, 2016; Lam & Chan, 2007), with one outlier assessing 46 items (Gonsalves et al, 2015). Seven studies used validated instruments to assess the use of pornography or violent pornography (Hald & Malamuth, 2015; Hughes et al, 2020; Huntington et al, 2022; Mikorski & Szymanski, 2017; Palermo et al, 2019; Rostad et al, 2019; Shin & Lee, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Taylor (2006) did not find an association between reading pornographic magazines and the presence of more aggressive sexual self-schema. Moreover, the acceptance of modern myths about sexual aggression was not significantly correlated with pornography consumption (de Heer et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Spanish study found that pornography consumption was associated with an increase in sexual risk behaviors in 47.4% of boys and 39.6% of girls [5]. In the US, inconsistent/irresponsible condom use was linked to pornography use in both boys and girls, with alcohol acting as a mediating factor in the association between pornography use and levels of victimization in young women [24], [25]. Loneliness may also be both a consequence and a predisposing factor for pornography use [18], [26].…”
Section: Sex Differences In Other Factors Related To Pornography Use ...mentioning
confidence: 99%
“…No significant differences were found in relation to age, gender, country, or design (correlational vs. longitudinal). In addition, significant longitudinal associations of frequency of pornography use with sexual victimization were found in different countries (e.g., [ 17 , 18 , 19 ]). Although support for a direct link between pornography use and sexual aggression perpetration has been questioned by a recent meta-analysis [ 20 ] and longitudinal studies from Croatia [ 21 , 22 ], other longitudinal studies have shown pornography use to be a moderator magnifying the link with other risk factors [ 23 ], or showing indirect associations via sexuality-related cognitions or behaviors [ 19 ].…”
Section: Introductionmentioning
confidence: 99%